Education Of Teacher's Knowledge And Skills In Washing Hands Of Soap In The Basic School Of The Region in Ponorogo - Fera Widyati, Tristya; Sari, Nia; Fazrin, Intan (Journal of Global Research in Public Health, 2019)
School-age children are those who are prone to various diseases, especially those related to the stomach. Children not doing hand washing with soap before eating will cause various disease-causing germs to enter the body easily. The role of the teacher in guiding how to wash hands properly and correctly plays a role in the level of health of students. The purpose of this study was to determine the effect of education on the knowledge and skills of teachers in hand washing using soap at the Elementary School in the Kauman Village area of ​​Ponorogo District. Quasi-experimental research design with pre-test and post-test design to determine teacher's knowledge and skills before and after being educated with counseling and simulation methods. The population in this study is all elementary school teachers in the area of ​​Kauman Village with a sample of 30 respondents in a simple random sampling. Data collection using questionnaires and assessment sheets on how to wash hands before and after education are then analyzed by Paired Sample T Test. The results of the study before being educated all respondents had less knowledge as many as 35 people (100%), after education of respondents who had good knowledge of 21 people (60%), only 14 people (40%). The respondents' skills before being educated were 12 people (34%) enough, 23 people (66%) lacking. After being educated as many as 25 people (72%) were good, 10 people (29%) were sufficient. The results of statistical tests showed differences in teachers' knowledge and skills before being educated and after being educated with sig (2-tailed) = 0,000 <0.05. After being educated there is an increase in teacher's knowledge and skills in hand washing. Good education can affect the teacher's knowledge in washing hands with soap which can be better too